1769 Occupational disease and morbidity modelling. (24th April 2018) - Samant, Y; Gravseth, HM; Aas, O; Ekle, R; Strømholm, T; Gigonzac, V; Khireddine-Medouni, I; Breuillard, E; Bossard, C; Guseva Canu, I; Santin, G; Chérié-Challine, L; et al.
Abstract : Aim of special session: To highlight examples and best practice in the area of occupational disease and modelling morbidity.